PjBL-STEM Integrated Multiple Representation-Based Digital Teaching Materials to Improve Problem-Solving in Chemical Equilibrium - Haryanto; Sutrisno; Winda Sitia Elisabeth Sinaga; Asrial; Wilda Syahri; Yusnaidar (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
Problem-solving skills can be achieved through the presentation of materials in teaching materials using models and approaches that guide students to solve problems related to the topic of chemical equilibrium. This research aims to develop integrated digital teaching materials based on PjBL-STEM with multiple representations, determine feasibility through expert validation, teacher assessment, student responses, and the effectiveness of teaching materials on problem-solving skills. This research and development (R&D) uses a multimedia design model. The results showed ratings in the very good category from material experts, media experts, teachers, and student responses. It is effective in enhancing problem-solving skills in the sub-topic of equilibrium concepts and equilibrium shifts, and sufficiently effective in improving problem-solving skills in the sub-topic of equilibrium constants.